2006
DOI: 10.1128/aem.03068-05
|View full text |Cite
|
Sign up to set email alerts
|

Immunoquantitative Real-Time PCR for Detection and Quantification of Staphylococcus aureus Enterotoxin B in Foods

Abstract: A real-time immunoquantitative PCR (iqPCR) method for detection of Staphylococcus aureus enterotoxin B (SEB) was developed and evaluated using both pure cultures and foods. The assay consisted of immunocapture of SEB and real-time PCR amplification of the DNA probe linked to the detection antibody. iqPCR was compared to an in-house enzyme-linked immunosorbent assay (ELISA) using the same couple of capturedetection antibodies and to commercial kits for detection of S. aureus enterotoxins (SE). The iqPCR was app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 19 publications
0
38
0
3
Order By: Relevance
“…In addition, DNA extracted from the milk sample combined with gene expression by RT-PCR analysis was highly sensitive for detection of enterotoxin Se A and Se B from undiluted and 10-fold diluted milk sample. Similarly, Rajkovic et al [25] detected Se B gene using RT-PCR from food sample, whereas other enterotoxin genes such as Se d, Se e, Se g, Se j, and Se i were also detected in some strains of S. aureus [26]. Likewise, reports showed that nine Se genes were detected with universal primers using SYBR green chemistry [27].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, DNA extracted from the milk sample combined with gene expression by RT-PCR analysis was highly sensitive for detection of enterotoxin Se A and Se B from undiluted and 10-fold diluted milk sample. Similarly, Rajkovic et al [25] detected Se B gene using RT-PCR from food sample, whereas other enterotoxin genes such as Se d, Se e, Se g, Se j, and Se i were also detected in some strains of S. aureus [26]. Likewise, reports showed that nine Se genes were detected with universal primers using SYBR green chemistry [27].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the RT-PCR method was also proved to be a successfully applicable technique for direct detection of Se from the clinical samples that contain high levels of PCR inhibitors [9]. Rajkovic also compared iqPCR with inhouse ELISA technique for detecting Se b toxin genes in both pure culture and contaminated food sample and found that iqPCR was approximately 1,000 times more sensitive than the in-house ELISA method [25]. Similarly, decade ago, Heller used the different available kit for comparing the sensitivity of the methods for DNA isolation from food samples for detection of Shiga toxin-producing Escherichia coli by RT-PCR [31].…”
Section: Resultsmentioning
confidence: 99%
“…In cases of infection with S. aureus, polymerase chain reaction (PCR) assays can determine the presence of the SE gene (Chiang et al, 2008;Rajkovic et al, 2006). Particularly in the case of a toxin that is known to be present in staphylococcal infections, surveillance and monitoring at the clinical level is imperative for differentiating between random outbreaks of the disease and a bioterrorist attack.…”
Section: Detection Of Ses and Sebmentioning
confidence: 99%
“…Alternatively, detection can be achieved through the enhancement of the generated chemiluminescence signal; it was reported that up to 1000-fold signal improvement can be achieved in the presence of certain molecules such as horseradish peroxidase. 4,5 Other signaling mechanisms reported include the 7 DNA reporters, 8,9 and fluorogenic reporters. 10,11 Electrochemical detection is considered as one of the most reliable and efficient techniques to detect biomolecules within biological samples.…”
Section: Introductionmentioning
confidence: 99%